“THE ROLE OF ARTIFICIAL INTELLIGENCE IN LEARNING ENGLISH” (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Artificial Intelligence (AI) is transforming modern education, especially foreign language learning. AI-powered technologies provide learners with personalized instruction, instant feedback, and interactive communication opportunities. This article examines the impact of AI on English language acquisition, discussing both its benefits and challenges in educational environments.
Keywords: In the 21st century, technology has become an inseparable part of education. Artificial Intelligence is one of the fastest-growing technologies influencing language learning worldwide. English learners increasingly use AI-based tools such as virtual assistants, grammar correction software, chatbots, and speech recognition applications.